2009
DOI: 10.1038/sj.bjc.6604967
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Mcm2, geminin and Ki67 in normal oral mucosa, oral epithelial dysplasias and their corresponding squamous-cell carcinomas

Abstract: Proteins necessary for the normal regulation of the cell cycle include minichromosome maintenance protein 2 (Mcm2) and geminin. These are overexpressed in several premalignant and malignant tumours. The Mcm2/Ki67 ratio can be used to estimate the population of cells that are in early G 1 (licensed to proliferate), and the geminin/Ki67 ratio can determine the relative length of G 1 . A high ratio indicates a short G 1 and a high rate of cell proliferation. Mcm2 and geminin have been scarcely explored in oral ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
91
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 30 publications
12
91
0
9
Order By: Relevance
“…It is present in S, G2 and M phases of the cell cycle, but absent in the G1 phase (20,21). Numerous previous studies examined the effect of Geminin expression on the overall survival of patients with breast, colorectal and prostatic cancers and showed that a higher expression of Geminin was a poor prognostic marker in patients with these types of cancer (33)(34)(35)37,38). On the other hand, Shrestha et al found that the relationship between Geminin expression and survival in patients with high-grade astrocytic tumors contradicted the previous findings (36), and that the overexpression of Geminin was associated with a longer survival of patients with high-grade astrocytic tumors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is present in S, G2 and M phases of the cell cycle, but absent in the G1 phase (20,21). Numerous previous studies examined the effect of Geminin expression on the overall survival of patients with breast, colorectal and prostatic cancers and showed that a higher expression of Geminin was a poor prognostic marker in patients with these types of cancer (33)(34)(35)37,38). On the other hand, Shrestha et al found that the relationship between Geminin expression and survival in patients with high-grade astrocytic tumors contradicted the previous findings (36), and that the overexpression of Geminin was associated with a longer survival of patients with high-grade astrocytic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The present study shows the prognostic significance of MCM7, Geminin and Ki-67, using immunohistochemical methods in 109 STSs. MCM proteins were reported to be correlated with the histologic grade in other types of cancer, including prostate cancer, lung adenocarcinoma and renal cell carcinoma (27)(28)(29)(30)(31)(32)(33)(34). We previously reported the positive relation between the expression of MCM2 and the prognosis of patients with human malignant fibrous histiocytoma (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After DNA replication is initiated during the cell cycle, Geminin inhibits re-uploading of the MCM proteins onto chromatin, thus preventing DNA re-replication in the same cell cycle (13). It has been confirmed that these proteins are useful biomakers that reflect the proliferative activity of the tumor cells and predict the survival of patients Multiparameter analysis using cell cycle biomarkers for small-size lung adenocarcinoma : Prognostic implications TOMOHIRO HARUKI 1,2 , KOHEI SHOMORI 1 , TATSUSHI SHIOMI 1 , YUJI TANIGUCHI 2 , HIROSHIGE NAKAMURA 2 and HISAO ITO 1 1 with various types of cancer (5)(6)(7)(8)(9)(10)(11)(14)(15)(16)(17)(18). Aurora A, known as a member of the serine/threonine kinase family, controls a subset of critical mitotic events including centrosome maturation and separation, as well as chromosome orientation and segregation (19).…”
Section: Introductionmentioning
confidence: 99%